Os direitos das crianças e dos adolescentes no cotidiano dos professores dos anos iniciais do ensino fundamental - Silva, Carlos Eduardo da (2018)
With main focus to the educational rights established in the Constitution of the Federative Republic of Brazil of 1988 (CRFB / 88), the Statute of the Child and Adolescent (ECA), the Law of Directives and Bases of National Education (LDB / 1996) and the Racial Equality Statute. This is a qualitative research, involving field research with application of questionnaires and documentary analysis. Fifty professionals participated voluntarily in the research, among them teachers, pedagogical coordinators and principals. After the data collection, the data were tabulated in a spreadsheet and categorized. The analysis indicates that there are gaps in the study of legislation, both in the initial and ongoing training of participants. Teachers state they have difficulty understanding and understanding these laws, and most say they do not have the skills or do not know what to do in case of suspected or confirmed maltreatment involving their students. The research also shows the lack of approach to the topic in the HTPCs and the lack of provision of continuing education courses in educational legislation maintained by the Public Power. Thus, we conclude that teachers of the reality investigated need a greater mobilization for the subject and that initiatives are carried out so that it is linked in its daily life. This incentive should be stimulated in the initial training courses and also be fostered in professional teaching experience, based on articulations between the management team and other organs of the Public Power , despite the existence of several laws aimed at guaranteeing the rights of children and adolescents, it is necessary to seek the effectiveness of legal norms in order to be able to defend and guarantee the rights of learners.